Anatomical variant of the meniscus related to posterior junction: a case report - David Sadigursky; Lucas Cortizo Garcia; Rodrigo Rêgo Martins; Gustavo Castro De Queiroz; Rogério Jamil Fernandes Carneiro; Paulo Oliveira Colavolpe (Journal of Medical Case Reports, 2017)
Abstract Background There are several reports on anatomical differences of the meniscus. However, there are only a few reports on abnormalities in both menisci and anatomical differences in anterior cruciate ligament insertions. Case presentation This is a case report of a 36-year-old Hispanic man presenting symptoms, including knee pain, locking, and effusion, with an anatomical abnormality of the menisci corresponding to the fusion of the posterior horns of the menisci in tandem with the insertion of the posterior meniscus fibers in the anterior cruciate ligament. Conclusions This is the first study describing a meniscus anatomical variant with isolated posterior junction of the posterior horn with an anomalous insertion to the anterior cruciate ligament. The recognition of meniscus variants is important as they can be misinterpreted for more significant pathology on magnetic resonance images.